Power primer a nontechnical guide from generation to end use - Chambers, Ann (Pennwell Pub., 1999)
Annotation "Penn Well's new Power Primer: A Nontechnical Guide from Generation to End-Use, offers a detailed look at how electricity is generated, transmitted, and distributed. Opening with an overview of electricity - what it is and how it works "from plant to plug" - the book then provides a history of the electric power industry. Section two explains generation - plants, components, and systems - and section three covers transmission and distribution - equipment, facilities, and their functions. The conclusion consists of an appendix that profiles the business, cultural, and political ramifications of deregulation."--BOOK JACKET.Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Keywords: Electric power production.; Electric power systems.; elektronické knihy; electronic books